2017
DOI: 10.1039/c6em00612d
|View full text |Cite
|
Sign up to set email alerts
|

Uranium mobility and accumulation along the Rio Paguate, Jackpile Mine in Laguna Pueblo, NM

Abstract: The mobility and accumulation of uranium (U) along the Rio Paguate, adjacent to the Jackpile Mine, in Laguna Pueblo, New Mexico was investigated using aqueous chemistry, electron microprobe, X-ray diffraction and spectroscopy analyses. Given that it is not common to identify elevated concentrations of U in surface water sources, the Rio Paguate is a unique site that concerns the Laguna Pueblo community. This study aims to better understand the solid chemistry of abandoned mine waste sediments from the Jackpile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 56 publications
1
63
0
Order By: Relevance
“…The sampling sites of plants were colocated with water and stream bank sediment samples that were studied by Blake et al during the same time period (Table S1). 14 Regional plants (grass, willow ( Salix ), and cattail ( Typha latifolia L. )), which are abundant at the site and may be used as cattle fodder or for ceremonial traditions, were sampled (Table S1). Detailed information for the sites and laboratory plant preparation is presented in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling sites of plants were colocated with water and stream bank sediment samples that were studied by Blake et al during the same time period (Table S1). 14 Regional plants (grass, willow ( Salix ), and cattail ( Typha latifolia L. )), which are abundant at the site and may be used as cattle fodder or for ceremonial traditions, were sampled (Table S1). Detailed information for the sites and laboratory plant preparation is presented in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical concentrations were measured using Inductively Coupled Plasma (ICP) – Optical Emissions Spectroscopy [15, 16, 1921], ICP – Atomic Emissions Spectroscopy [15, 16, 19, 20], ICP – Mass Spectroscopy [13, 1517, 1924], or Graphite Furnace Atomic Absorption Spectroscopy [18]. Additionally, concentrations of As, U, chromium (Cr), lead (Pb), iron (Fe), and vanadium (V) were measured in mine waste, soil, sediment and other solid material using x-ray fluorescence [21, 22], X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy [21]. ICP-MS was also used to measure As, U, Cd, selenium (Se), Pb, and molybdenum (Mo) was measured in soil and uptake in grasses consumed by sheep [25].…”
Section: Resultsmentioning
confidence: 99%
“…Minimal seasonal/temporal variability was reported for As and U measured in UWSs in the Arizona portion of Navajo Nation [23], and UWSs across the Navajo Nation [19]. Blake et al (2017) observed As concentrations less than 10 μg/L in replicate surface water sources located downstream of a U mine in New Mexico [22]. In the same samples however, U concentrations ranged between <LOD and >700 μg/L and exhibited a strong season effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the solubility constant (K sp ) is related to the soluble species activity raised to the power of their molar coefficient. 27 This is compared to that of groundwater near Shiprock, NM that had concentrations of HCO 3 between ~100-1500 mg/L (pH's between 6.4 and 7.7) 6 where CO 3 2would be at ~ 0.5% of these concentrations (0.5-7 mg/L). At such high concentrations in surface waters and ground waters, carbonates can compete with uranium hydrolysis products, creating highly soluble uranyl carbonate species and contributing to enhanced mobility of uranium in the environment.…”
Section: Uranium Legacy Contamination Within the Navajo Nationmentioning
confidence: 99%